THE EFFECTIVENESS OF RRB (ROUND ROBIN BRAINSTORMING) COOPERATIVE LEARNING METHOD TO IMPROVE STUDENTS’ READING COMPREHENSION OF TENTH GRADE AT SMK NEGERI 1 NGANJUK - Heny Agustin; Rina Puji Utami (Universitas PGRI Mpu Sindok, 2025)
Reading comprehension is one of the important skills in English language learning. However, there are still many students who experience difficulties in reading comprehension. Students have difficulty answering questions related to reading such as lack of interest in reading, difficulty in interpreting context and making conclusions in the text. The aims of this research are :To find out there any significant different before and after being taught by using RRB (Round Robin Brainstorming) Cooperative Learning method in the teaching reading. The research is Quasi Experimental research with a quantitative approach . The design used in this research is pre-test and post-test (One Group Pre-Test and Post-Test). This research was conducted at SMKN 1 Nganjuk in the 2023/2024 school year, using a population of all tenth grade classes, the sample used by researchers was class X Geomatic 2 consisting of 35 students. The sampling technique used convenience sampling. Data collection in this research using tests. The data analysis technique used in this study used the t-test. The results of this research showed that students obtained an average pre-test score of 53.42 and an average post-test score of 83.71. Based on the results of the analysis obtained the value of t-count = 15.60 and t-table = 1.691, t-count> t-table which means there is Ha accepted and H0 rejected. So “There is significant different before and after being taught by using RRB (Round Robin Brainstorming) Cooperative Learning method effectiveness to improve students’ reading comprehension of tenth grade at SMK Negeri 1 Nganjuk in the academic year of 2023- 2024”.